Design of Air Conditioning Systems - Abdulkhaev, Zokhidjon; Shairakhon, Abdujalilova (Journal of Engineering Science and Technology, 2024)
Climate change is one of the most pressing global problems today. Today, global warming is observed throughout the earth. As a result, the design of the natural ventilation system in the rooms does not meet the sanitary and hygienic requirements for the ventilation system. Designing an air conditioning system, choosing the right air conditioners requires the necessary knowledge and skills. Today there are many types of air conditioners. What parameters are taken into account when choosing air conditioners, what calculations are made.